2014
DOI: 10.1002/jaal.329
|View full text |Cite
|
Sign up to set email alerts
|

Critical Literacy as Policy and Advocacy

Abstract: This article, the first column for this issue's Policy and Advocacy department, features a discussion about a recent experience in a graduate program in Medellín, Colombia introducing students to critical literacy. Graduate students used ideas from critical literacy to engage in an in‐depth analysis of textbooks they had used in their practice. Their reflexivity showed that they raised questions about teachers' attachment to textbooks, the meaning of critical consciousness, issues of ideology in those textbook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
0
14
0
1
Order By: Relevance
“…La definición de literacidad que se presenta en este estudio va más allá del enfoque lingüístico y cognitivo y significa siguiendo a los Nuevos Estudios de Literacidad (NEL) (Street 1984;Barton y Hamilton, 1998;Gee 1996), como representantes de una nueva tradición, la existencia de una forma adicional de comprenderla, desde una perspectiva social. Esta nueva mirada se ha venido desarrollando desde la década de los años 80 principalmente en Inglaterra, y con estudios en Latinoamérica e Iberoamérica (Viñao, 1998;Zavala, 2008;Mora, 2014, Lorenzatti, 2014López Bonilla y Fragozo, 2013) que se identifican con el modelo ideológico de Street (1984). En este sentido, los NEL muestran un enfoque diferente al tradicional, ya que se pensaba que la literacidad era un fenómeno mental o cognitivo únicamente, y este movimiento presenta el significado de leer y escribir en relación con lo que la gente hace en el mundo o en la sociedad, es decir, la lectura y la escritura como práctica, o actos socioculturales a través de los cuales los ciudadanos desarrollan una actividad vital en una comunidad letrada, de manera integral en todos sus contextos y prácticas, es decir en lo social, cultural, histórico e institucional.…”
Section: Otros Antecedentes: Literacidadunclassified
“…La definición de literacidad que se presenta en este estudio va más allá del enfoque lingüístico y cognitivo y significa siguiendo a los Nuevos Estudios de Literacidad (NEL) (Street 1984;Barton y Hamilton, 1998;Gee 1996), como representantes de una nueva tradición, la existencia de una forma adicional de comprenderla, desde una perspectiva social. Esta nueva mirada se ha venido desarrollando desde la década de los años 80 principalmente en Inglaterra, y con estudios en Latinoamérica e Iberoamérica (Viñao, 1998;Zavala, 2008;Mora, 2014, Lorenzatti, 2014López Bonilla y Fragozo, 2013) que se identifican con el modelo ideológico de Street (1984). En este sentido, los NEL muestran un enfoque diferente al tradicional, ya que se pensaba que la literacidad era un fenómeno mental o cognitivo únicamente, y este movimiento presenta el significado de leer y escribir en relación con lo que la gente hace en el mundo o en la sociedad, es decir, la lectura y la escritura como práctica, o actos socioculturales a través de los cuales los ciudadanos desarrollan una actividad vital en una comunidad letrada, de manera integral en todos sus contextos y prácticas, es decir en lo social, cultural, histórico e institucional.…”
Section: Otros Antecedentes: Literacidadunclassified
“…These columns were intended to open a space for larger, more global conversations about literacy. Although Colombia in particular (Mora, , ) and Latin America in general (López‐Bonilla, ) were the focal point of most columns, we also opened discussions about Africa (Njeru, ), rural contexts (Azano, ), and the global effect of online forums for literacy (Angay‐Crowder et al., ). To the JAAL editors, I only have words of gratitude for opening a space for me to share our global concerns and local proposals.…”
Section: A Global Call For Policy and Advocacymentioning
confidence: 99%
“…As one of those scholars from and in the south, I have faced some of the issues that Kress pointed out in his text. I have also faced what is a very interesting moment for the field in Colombia (Mora, ) and, more specifically, in Latin America at large.…”
mentioning
confidence: 99%
“…It needs to take into account the current social and political conditions with the purpose of helping students and teachers understand and act upon those conditions. In a study that was carried out in Colombia, Mora (2014) introduced graduate students to critical literacy by engaging them in the in-depth analysis of textbooks. The result of the study indicated four issues in the students' analysis: (a) breaking the attachment to the textbooks as a precursor to critical literacy, (b) developing a more critical consciousness, (c) questioning the status quo in the textbooks, and (d) viewing themselves as advocates.…”
Section: Critical Literacymentioning
confidence: 99%